Territorial marketing in Parque das Nações: diagnosis of the resident population in Centieira Street (Revista Lusófona de Economia e Gestão das Organizações, 2016)
The cities or territories must from a diagnosis of its characteristics to identify the cities with which they compete and examine the type of consumers interested in the attributesthat the city can offer (Franco, 2011).In a City Marketing perspective and sustainability of the territory of Parque das Nações parish in Lisbon, where World Exposition EXPO 98 took place, there is a street with historic features, with needs to be rehabilitate and that was added in the new parish of Parque das Nações, created in November 2012.This paper aims to make the population of the Centieira Street diagnosis, their characteristics, their sense of belonging (Azevedo, Magalhães and Pereira, 2010) and what they want to see future designed at this location: namely, to recover the historical perspective and keep a typical street of old Lisbon at Parque das Nações, or rebuild, similar to what happened in the modernized area of Parque das Nações.At an urban marketing level, actions must be designed so that there is a common thread, and in which the objective is to promote the territory internally and externally (Franco, 2011). For these stages go through, there is an initial work that this paper sets out to achieve.